Research on the Status of Gratitude Therapy of High School Students in Da Nang City - Uyen, Tran Nguyen Chau; Mai, Ho Tran Nhu; Trang, Ms. Le Phan Quynh (RA Journal of Applied Research, 2021)
Gratitude is an extremely necessary spiritual element in our lives. Grateful people experience life in a more peaceful, and happy way. The study was conducted on 762 students from two clusters of gifted and non-specialized high schools in Da Nang city to describe the current situation, perception of gratitude and factors affecting the level of gratitude in high school students. Research results show that 79% of students are not grateful. A special thing is that the factors such as academic ability, age, and gender do not completely affect the gratitude level of high school students. Based on the findings, the study proposes a number of measures that partially affect the educational methods of schools and families, as well as directly affect the survey subjects.